The Moral Hazard and the Regulation of the Quality of Public Services - Viveros Zuazo, Aresio Antonio (2015)
One of the main purposes of a Regulatory Agency is to monitor the quality of the service that regulated companies provide to its final users, in order to achieve an improvement in its performance and verify compliance with minimum quality standards that legislation impose on the concessionaires of public services.Given the asymmetry of information that tends to exist between the companies providing public services and the regulator, the decision by the latter allows them to reduce the costs that must be incurred to provide a service with appropriate quality standards, in order to maximize their benefits; and prevents the regulator to oversee such a service and take necessary corrective actions for the population. This conflict of interest is known as moral hazard.This article identifies and describes the situations in which moral hazard can occur, proposing the use of incentives to resolve the conflict.